Building Competitive Firms : Incentives and Capabilities - Nabi, Ijaz; Luthria, Manjula (Washington, DC: World Bank, 2013)
This publication presents a framework that emphasizes the economic and policy incentives needed to create competitive firms and national economies. It also explains the key capabilities that firms must develop in-house in order to become more competitive. The framework provides a link between important policy issues such as corporate governance, foreign direct investment, innovation readiness, intellectual property rights, e-commerce, skill training, and supply chain management. The papers presented here emphasize that, while individual firms must take the lead in enhancing competitiveness, the role of public policy remains vital. This book also presents examples of private effort and public policies that exemplify the lessons drawn from international experience in designing policies and institutions that strengthen competitiveness in industrializing countries.